Peran Brand Image dan Brand Trust dalam Meningkatkan Purchase Decision melalui Customer Satisfaction sebagai Variabel Intervening pada E-Commerce Lazada - Muhammad Labibul Mukhtar; Erma Sri Hastuti (Lembaga Yasin AlSys, 2026)
Although e-commerce competition in Indonesia has become increasingly intense, studies on the mechanisms through which brand image and brand trust influence purchase decisions through customer satisfaction as an intervening variable remain relevant, particularly among Lazada users amid a declining trend in market share and consumer purchase decisions. This study aimed to analyze the effects of brand image and brand trust on purchase decisions with customer satisfaction as an intervening variable among Lazada e-commerce users. The study employed a quantitative approach with an explanatory research design and involved 100 Lazada users selected through purposive sampling. Data were collected using a questionnaire and analyzed with SmartPLS 4 through descriptive statistical analysis, outer model evaluation, and inner model evaluation. The results showed that brand image and brand trust had positive and significant effects on customer satisfaction and purchase decisions. Customer satisfaction also had a positive and significant effect on purchase decisions and was proven to mediate the effects of brand image and brand trust on purchase decisions. These findings affirm that brand image and brand trust are important factors in building customer satisfaction, which subsequently drives consumer purchase decisions on Lazada. This study contributes to strengthening the understanding of the mediating role of customer satisfaction in the relationships among brand image, brand trust, and purchase decisions and provides practical implications for e-commerce managers to strengthen brand image and brand trust as strategies for increasing customer satisfaction and consumer purchase decisions.